Banque Centrale Et Politique Budgetaire : Une Ã‰vidence Empirique Pour La Zone CEMAC - Dessy-Karl, Tadadjeu Wemba; FranÃ§ois, Kamajou; Gilbert, Noula Armand (European Scientific Journal, ESJ, 2018)
The purpose of this article is to analyze how the degree of independence of the Bank of Central African States (BEAC) influences the level of budget deficit for the countries of the Economic and Monetary Community of Africa Centrale (CEMAC) over the period 1994-2016. To do this, we rely on the statutory and rotational indicators of central bank governors developed by the literature, as well as on the econometrics of panel data. The results of the estimates indicate a mixed relationship between degree of independence and level of budget deficit. This result can be interpreted as an absence of constraint on fiscal policy, or as the partial assumption of cyclical stabilization by the central bank even when it is independent. It can also be interpreted as an absence of obligation for the budgetary policy to take charge of the cyclical adjustment. These results nevertheless confirm that the average orientation of fiscal policy is determined more by the budget procedure itself than by the statutes and the government of BEAC.